A 3D printed synergistic aerogel microreactor toward stable and high-efficiency photocatalytic degradation. (December 2021) - Wang, Y.; Zhang, Y.; Wang, S.; Guan, Y.; Zhang, Y.
Abstract: Photocatalysis offers a credible and prompt approach to solving the growing problems of environmental pollution and energy shortages. However, the practical application of photocatalytic materials still faces the challenge of the efficient catalytic system without secondary recovery. Herein, hollow Fe2 O3 microspheres with uniform size (polydispersity index = 0.067) were synthesized using an innovative microgel template–assisted solvothermal method with high yield. Via direct writing three-dimensional printing, the as-prepared Fe2 O3 microspheres and graphene oxide were fabricated into an ultralight, stable, and high-performance aerogel microreactor, achieving wastewater treatment without catalyst recovery. Photocatalytic degradation efficiency of rhodamine B achieved 97.8% by the microreactor under simulated sunlight irradiation for 120 min. The rich porous structures and highly interconnected networks of the microreactor provide high specific surface area and increased numbers of multidimensional mass transfer channels, further enabling the catalytic performance and reusability for photocatalytic degradation. Graphical abstract: Image 1 Highlights: New soft template method for the synthesis of size-homogeneous hollow microspheres. 3D printed ultralight Fe2 O3 /graphene microlattice aerogel with high specific surface area. High efficiency photocatalytic degradation system without recycling of catalyst particles.